Defending the Revolution through Labor Organization and Spontaneity in the Committees for the Defense of the Revolution in Cuba, 1961–1965 - Juan Carlos Medel (Latin American Research Review)
The Committees for the Defense of the Revolution (CDR) were one of the most important mass organizations in revolutionary Cuba. During the 1960s, the CDR developed a slew of actions among the Cuban masses, organizing cultural, political, and economic activities that shaped the revolutionary process from below. Through their work, the CDR gave meaning to their own idea of Cuban socialism. In the context of revolutionary upheaval, they were born as mass organizations to organize political surveillance against counterrevolutionary enemies. But the CDR also deployed productive power that sought to improve the lives of fellow Cubans. Organizing workers to solve local problems helped to reimagine the purpose of labor as a resource for public utility. For moments, the CDR even became the state. This article highlights the crucial role of the CDR members in the revolutionary process and their impact on the everyday lives of Cuban people.